Emergency response analysis for humanitarian logistics. - Ignatius, Joshua

(untitled)
In Malaysia, there are four main types of disasters, which are landslide, hurricane/strong winds, flood and flash flood. Among the four disasters, flood has the highest occurrence from the year 2010 to the year 2015. In Kelantan, flood is an annual occurrence of varying severities.